Program Tafaqquh Takhasus Arobiyyah: Analisis dan Evaluasinya - Hasan Syukur (P3M STAI MIFTAHUL ULUM LUMAJANG, 2024)
Program evaluation is one of the important components in the management of a program. Evaluation aims to determine the extent to which a program has achieved the goals that have been designed. This study aims to: 1) find out how the Tafaqquh Takhasus Arobiyyah program is implemented at LPD Al-Bahjah Cirebon, 2) Find out how the evaluation is carried out on the tafaqquh takhasus arobiyyah program at LPD Al-Bahjah Cirebon. This research uses descriptive qualitative research method. Data were obtained through several data collection techniques, namely through observation, interviews and documentation. The technique used to analyze the data is data reduction, data presentation and then verification or drawing conclusions. The results of this study provide an explanation that: 1) the Tafaqquh takhasus arobiyyah program at LPD Al-Bahjah Cirebon is one of the flagship programs at LPD Al-Bahjah Cirebon. This program is a program that has been well managed. This can be seen from the existence of clear goals, neat structures, good implementation and also good cooperation between managers. 2) The evaluation carried out on the Tafaqquh Takhasus Arobiyyah program at LPD Al-Bahjah Cirebon focused on three parts, namely evaluation of program design, program implementation and program results. The absence of indicators for assessment materials from the evaluation of the program is something that needs to be considered considering that it is very important to be taken into consideration in the assessment for evaluation.